Hydrodynamic resistance of the rotational filter of the improved design - Мочалин, Евгений Валентинович (Eastern-European Journal of Enterprise Technologies, 2012)
The analytic formulas for estimation of pressure drop on the rotary filter for mechanical cleaning of liquids are obtained. The fundamentals of design calculation of improved filters with low hydraulic resistance are supplemented